Public Funding for Science and the Value of Corporate R&D Projects; Evidence from Project Initiation and Termination Decisions in Cell Therapy. (21st December 2018) - Huang, Hsini; Jong, Simcha
Abstract: How do firms decide which R&D projects to pursue and which ones to cast aside? We use a real options approach to advance our understanding of how firms manage uncertainties in R&D project management, in particular uncertainties linked to the external scientific environment. Our findings highlight how these uncertainties have an impact on the initiation and discontinuation of R&D projects. We examine these effects in the context of shifts in US science policy in the cell therapy field, using a dataset on 570 R&D projects in the global cell therapy sector, initiated over the period 1986–2011. We find decreased R&D project initiation rates and higher discontinuation rates for projects initiated by US firms in the aftermath of policy shifts that increased uncertainties about public funding support for US cell therapy research. We also highlight how this effect was reversed as the US public funding outlook for such research recovered.